Spirometric Standards for Healthy Children Aged 6-15 Years in a School of Dhaka City, Bangladesh - Mazumder, JU; Ahmed, S; Mollah, AH; Kabir, ARML; Nahar, N (Bangladesh Journal of Child Health, 2010)
Background: Prevalence of Asthma in children is about 7% in Bangladesh but Spirometric value of children is not available. Objective: The study was conducted to find out the spirometric value of normal school going children and to compare the values with those of other countries. Methodology: Sprirometric evaluation of normal school going children was done by computerized spirometer (Ponygraphic of COSMED srl-ltaly) in a school of Dhaka city during the period of February 2002 to July 2002. Nine hundred twenty seven healthy children aged 6-15 years were selected for the study. Outcome variable were the forced vital capacity (FVC), forced expiratory volume in first second (FEV1), peak expiratory flow (PEF), the ratio of FEV1 to FVC and forced expiratory flow (FEF) between 25% & 75% of vital capacity (FEF 25% & 75% ). The pulmonary function data was separated by sex and categorized on the basis of height, weight, age and body surface area. The mean and standard deviation were calculated for every such variable. The results (FVC) of present study was compared with those of other countries (India, Nigeria, British and America). Results: The lung function variables showed a linear positive correlation with height, weight, age and body surface area (independent variables). Strong correlation was found between lung function values and independent variables. Height showed the maximum correlation in comparison with other variable. Forced vital capacity (FVC) and FEV1 showed a spurt after the height of 150 cm. Regression equations for lung function values were determined for boys and girls considering height as independent variable. Boys showed higher values for lung functions than those of girls. Lung function values of these studied children are nearly similar to Indian children and significantly lower than Nigerian, British (UK) and American (USA) peers. Conclusion: Spirometric values of our children are very much comparable with those of regional children (India) but values are lower than those of African (Nigeria), European (British) and American (USA) children. Recommendation: Further study should be done with larger sample size to have our own national data and to fill up the standard spirometric values for the children of our country. Key words: Spirometric standards; healthy children. DOI: 10.3329/bjch.v29i3.6187 Bangladesh J Child Health 2005; Vol 29 (3): 93-98